Born Under COVID-19 Pandemic Conditions: Infant Regulatory Problems and Maternal Mental Health at 7 Months Postpartum - Perez, Anna; Göbel, Ariane; Stuhrmann, Lydia Yao; Schepanski, Steven; Singer, Dominique; Bindt, Carola; Mudra, Susanne (Frontiers in Psychology, 2022)
Background: The SARS-COVID-19 pandemic and its associated disease control restrictions have in multiple ways affected families with young children, who may be especially vulnerable to mental health problems. Studies reported an increase in perinatal parental distress as well as symptoms of anxiety or depression in children during the pandemic. Currently, little is known about the impact of the pandemic on infants and their development. Infant regulatory problems (RPs) have been identified as early indicators of child socio-emotional development, strongly associated with maternal mental health and the early parent-infant interaction. Our study investigates whether early parenthood under COVID-19 is associated with more maternal depressive symptoms and a differing perception of their infants as having more RPs regarding crying/fussing, sleeping, or eating, compared to mothers assessed before the pandemic. Methods: As part of a longitudinal study, 65 women who had given birth during the first nationwide disease control restrictions in Northern Germany were surveyed at 7 months postpartum and compared to 97 women assessed before the pandemic. RPs and maternal depressive symptoms were assessed by maternal report. Number of previous children, infant negative emotionality, and perceived social support were assessed as control variables. Results: Compared to the control cohort, infants born during the COVID-19 pandemic and those of mothers with higher depressive symptoms were perceived as having more sleeping and crying, but not more eating problems. Regression-based analyses showed no additional moderating effect of parenthood under COVID-19 on the association of depressive symptoms with RPs. Infant negative emotionality was positively, and number of previous children was negatively associated with RPs. Limitations: Due to the small sample size and cross-sectional assessment, the possibility for more complex multivariate analysis was limited. The use of parent-report questionnaires to assess infant RPs can support but not replace clinical diagnosis. Conclusions: The pandemic conditions affecting everyday life may have a long-term influence on impaired infant self- and maternal co-regulation and maternal mental health. This should be addressed in peripartum and pediatric care. Qualitative and longitudinal studies focusing on long-term parental and infant outcomes under ongoing pandemic conditions are encouraged.